Productivity of deverbal suffixal nouns in the Joint Corpus of Lithuanian - Pakerys, Jurgis; Navickaitė-Klišauskienė, Agnė; Dadurkevičius, Virginijus (Baltistica, 2024)
We use the Joint Corpus of Lithuanian (1.3 billion tokens) to estimate the derivational productivity of the main suffixes of deverbal nouns in Lithuanian. We measure their realized, expanding, and potential productivity (Baayen 1992; 1993) and compare our rankings to the ones found in the main grammars and studies of neologisms. In general, the ordering of the suffixes according to their realized and expanding productivity is similar to the one found in earlier studies. The rankings according to potential productivity, however, in many cases proved to be less usable because suffixes with lower total frequencies of their formations appear to be overestimated when compared to suffixes having high total frequencies.
Keywords: Lithuanian; deverbal nouns; suffixal nouns; derivational productivity; realized productivity; expanding productivity; potential productivity; corpus linguistics